LA-iMageS - López-Fernández, Hugo (2018)
The authors thank the Fundacao de Amparo a Pesquisa do Estado de Sao Paulo (FAPESP, Sao Paulo, Brazil), the Conselho Nacional de Desenvolvimento Cientifico e Tecnologico (CNPq, Brasilia, Brazil), the Coordenacao de Aperfeicoamento de Pessoal de Nivel Superior (CAPES, Brasilia, Brazil), and the INOU-16-05 project from the Provincial Council of Ourense for financial support and fellowships. Dr. Capelo acknowledges support given by the Associate Laboratory for Green Chemistry LAQV which is financed by national funds from FCT/MEC (UID/QUI/50006/2013) and co-financed by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-007265), and by the Unidade de Ciencias Biomoleculares Aplicadas-UCIBIO which is financed by national funds from FCT/MEC (UID/Multi/04378/2013) and co-financed by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-007728). H. Lopez-Fernandez is supported by a postdoctoral fellowship from Xunta de Galicia. SING group thanks CITI (Centro de Investigacion, Transferencia e Innovacion) from University of Vigo for hosting its IT infrastructure.